The Effectiveness of the Transmission Mechanism’s Credit Channel: A Case Study of the Visegrad Four Countries - Černohorská, Liběna; Kalibánová, Pavlína (Springer Nature Switzerland AG, 2024)
This article aims to evaluate the impact of the transmission mechanism’s credit channel in the countries of the Visegrad Four (V4) for the period of 2007 to 2021. The analysis examines the dependence between the selected central banks’ interest rates and the amount of loans provided to nonfinancial business entities (loans) and subsequently the dependence between loans and gross domestic product (GDP) in the V4 countries. The analysis is conducted using time series analysis. The empirical results did not indicate the presence of long-term relationships between the selected variables for the V4 countries. In all the V4 countries, a mutual short-term relationship was seen between the given country’s basic central bank interest rates and the amount of loans provided to non-financial business entities and, at the same time, between loans and GDP. On the basis of these results, it can be stated that the monetary policy transmission mechanism’s credit channel is effective in the V4 countries only in the short term. Monetary policy’s credit transmission mechanism was seen to operate both for the autonomous central banks—in the Czech Republic, Poland, and Hungary—as well as for the National Bank of Slovakia, which is subject to the European Central Bank’s policy.
Účinnost úvěrového kanálu transmisního mechanismu: Případová studie zemí Visegrádské čtyřky
Keywords: Central bank; Credit channel; Granger causality; Monetary policy; The Visegrad group; Transmission mechanism; Centrální banka; Úvěrový kanál; Grangerova kauzalita; Měnová politika; Visegrádská skupina; Transmisní mechanismus